2020
DOI: 10.1002/ep.13490
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics modeling of ibuprofen removal using a hollow fiber membrane contactor

Abstract: In this study, modeling and simulation of removing a common pharmaceutical contaminant by a hollow fiber membrane contactor (HFMC) were carried out. For this purpose, a model was presented for separation of ibuprofen from wastewater in the membrane contactor. The suggested model was developed by coupling the mass and momentum equations. The partial differential equations (PDEs) and the corresponding boundary conditions of the model were solved using the computational fluid dynamics (CFD) techniques. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As it can be seen, the contribution of convective flux along the membrane contactor is significant in comparison with axial diffusive flux and the convective flux is maximum in the centre of the shell side where the gas velocity is maximum. This could be due to the fact that the velocity is predominant which can result in high convective flux 38 . Figure 6 illustrates that both diffusive and convective fluxes are reduced along the fiber length because of reducing the driving force in the z -direction.…”
Section: Resultsmentioning
confidence: 99%
“…As it can be seen, the contribution of convective flux along the membrane contactor is significant in comparison with axial diffusive flux and the convective flux is maximum in the centre of the shell side where the gas velocity is maximum. This could be due to the fact that the velocity is predominant which can result in high convective flux 38 . Figure 6 illustrates that both diffusive and convective fluxes are reduced along the fiber length because of reducing the driving force in the z -direction.…”
Section: Resultsmentioning
confidence: 99%
“…When the number of membrane fibers is small and the geometry in the membrane device is simple, the simulation results are more reliable. Deriss et al 16 established a two‐dimensional mathematical model to simulate the mass transfer performance of octanol absorption of ibuprofen. The results show that the relationship between the outlet concentration and the fiber number is not linearly proportional, and the increase of fibers provides a high contact area and promotes mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they found that increasing liquid flow rate, temperature, concentration, and reducing gas flow rate enhanced CO 2 absorption. The separation of ibuprofen from wastewater via a membrane contactor was simulated by Deriss et al 12 They found that increasing the length of the fibers and the porosity of the membrane enhanced the ibuprofen removal. Darabi et al investigated a 2‐D mathematical simulation using the FDM method for CO 2 mass transport from a mixture of gas in the presence of carbon nanotube (CNT) NPs and Silica in an HFMC according to the non‐wetting mode 13 .…”
Section: Introductionmentioning
confidence: 99%